ORGANIZATION OF THE PRIMARY SEED BREEDING OF THE LARGE SEED "ZABARDAST" VARIETY OF PEAS FOR EXPORT - Nahalboev Jahongir Tursunboevich (Journals Park Publishing, 2025)
This article presents information on the morphological characteristics of ridges in the fields of annual generations of the chickpea variety "Iftikhor".
Keywords: Chickpea, generation, morphological features, nursery, seed productivity, annual generation, family.